Exploring the relationship of supernumerary recurrent renal calculi formation and tick-borne infections: a case report - Paz, Dean C.; Gunther, Abigael C.; Higham, Michael C.; Stephenson, Lynne G.; Laporta, Anthony J.; Gubler, K. Dean; Ryznar, Rebecca J. (Frontiers in Cellular and Infection Microbiology, 2024)
A 51-year-old male with a history of Cacchi-Ricci disease and long-standing infection with various species of Borrelia, Babesia, and Bartonella presented with recurrent symptoms of rightsided flank pain. Numerous renal calculi were identified on imaging. The etiology of the calculi had not been previously elucidated. Symptoms intermittently date back to 2002 when uric acid stones were identified. Subsequent calculi analysis revealed calcium oxalate stones. Despite the commonality of nephrolithiasis in patients with Cacchi-Ricci disease, the extreme number of calculi and recurrent presentation of symptoms persisted despite a plethora of medical evaluations, dietary changes, and hereditary testing. This case raises questions of etiology including possible immune deficiency and whether his uncommon microbial history contributes to recurrent stone formation.